2012
DOI: 10.1002/app.37853
|View full text |Cite
|
Sign up to set email alerts
|

The shearing effect on hydrophobically associative water‐soluble polymer and partially hydrolyzed polyacrylamide passing through wellbore simulation device

Abstract: Hydrolyzed polyacrylamide (HPAM) was the traditional polymer and hydrophobically associative water-soluble polymer (HAWP) was the new polymer with three-dimensional network both used to flood to enhance oil recovery. The wellbore area was the most important part before the polymer solution injected into stratum. In this article, the shearing effects of the two polymers were studied by a wellbore simulation device. The viscosities of HPAM and HAWP solutions were both decreased around perforation of wellbore sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…For the AFM measurements, 0.1 mL of the prepared polymer-surfactant mixed system was dropped onto freshly cleaved mica, and the redundant solution was blown off by a stream of high purity nitrogen. Samples were measured by Nanoscope IIIa microscope in air at the ambient temperature [30].…”
Section: Measurement Of Molecular Aggregation Morphologiesmentioning
confidence: 99%
“…For the AFM measurements, 0.1 mL of the prepared polymer-surfactant mixed system was dropped onto freshly cleaved mica, and the redundant solution was blown off by a stream of high purity nitrogen. Samples were measured by Nanoscope IIIa microscope in air at the ambient temperature [30].…”
Section: Measurement Of Molecular Aggregation Morphologiesmentioning
confidence: 99%
“…The polymer with three-dimensional network (ANOB) can reform network at slower shearing rate by self-assembly of hydrophobic groups. [18] Thus, the viscosity of ANOB solution can recover efficiently. It can be inferred that the sheared ANOB solution can also be used to flood in oilfields.…”
Section: Effect Of Shearing On Viscositymentioning
confidence: 98%
“…[18] Thus, the apparent viscosity was adopted as the main index for evaluation of rheological properties of polymer. Figure 6 presents the apparent viscosity changes of polymer solutions with temperature under a definite concentration of 1000 mg/L.…”
Section: Thickening Property Of Polymermentioning
confidence: 99%
“…A different HMC based on an aromatic hydrophobe is discussed by Zhang et al (Zhang et al 2011). The shearing effect during injection of a HMC compared to a standard APAM was studied with simulation techniques (Zhang et al 2013). In this evaluation it was shown that APAM is shear degraded seriously, while the HMC is also degraded to a certain extent, but recovers after the shear had stopped and maintains a good performance.…”
Section: Hydrophobically Modified Copolymers (Hmc)mentioning
confidence: 99%